Study on Soil Mobility of Two Neonicotinoid Insecticides - Mária Mörtl; Orsolya Kereki; Béla Darvas; Szandra Klátyik; Ágnes Vehovszky; János Győri; András Székács (Journal of Chemistry)
Movement of two neonicotinoid insecticide active ingredients, clothianidin (CLO) and thiamethoxam (TMX), was investigated in different soil types (sand, clay, or loam) and in pumice. Elution profiles were determined to explore differences in binding capacity. Soil characterized by high organic matter content retained the ingredients, whereas high clay content resulted in long release of compounds. Decrease in concentration was strongly influenced by soil types: both CLO and TMX were retained in loam and clay soils and showed ready elution through sandy soil and pumice. Elution capability of the active ingredients in sandy soil correlated with their water solubility, indicating approximately 30% higher rapidity for TMX than for CLO. Soil organic carbon-water partitioning coefficients (Koc) determined were in good agreement with literature values with somewhat lower value for CLO in sandy soil and substantially higher values for TMX in clay soil. High mobility of these neonicotinoid active ingredients in given soil types urges stronger precautionary approach taken during their application.